Experimental verification of the model of preparation of future social educators for communicative activity in the rest camps - SYDORENKO, Olena (Journal of Education, Technology and Computer Science, ISSN 2719-6550, e-ISSN 2719-7417, 2013)
The model of preparation of future social teachers to communicative activityin the rest camps are described in the article. The results of the forming experimentare analyzed